Measurement Models of Intellectal Capital for the Decision Making and Performance Variables (Global Journal of Management and Business Research, 2015)
This article aims in making a model review for measurement of intellectual capital for decision making. The construction of the present article was made through the bibliographic survey covering the Intellectual Capital theme addressing its objectives, peculiarities and definitions. It has been presented a classification of the methods from Sveiby#x2019;s (2011) perspective, as well as 30 models for evaluation of the Intellectual Capital. It can be concluded that the models differ by its application context, considered assets and set of indicators of measurement, for better decision making.
Keywords: intellectual capital; intangible assets; measurement methods